PENGARUH ETIKA AUDITOR TERHADAP KUALITAS AUDIT (Survey pada Auditor di Kota Jakarta) - Hendrick, Fransisca Fauziyah; Harahap, Devianti Yunita (Jurnal Ekonomi dan Bisnis, 2019)
The purpose of this study is to determine whether integrity, objectivity, competence, confidentiality, and professional behavior positively affects audit quality, either simultaneously or partially. In this research, the independent variables are integrity, objectivity, competence, confidentiality, and professional behavior. The dependent variable is audit quality.The survey method has been applied on the respondent to auditors of Jakarta City. The study respondents are 92 auditors of 20 public accounting firm in Jakarta. Collecting data was conducted by questionnaire. This study used path analysis to analyze the data. The result of the study show that integrity, objectivity, competence, confidentiality, and professional behavior simultaneously and partially positively affects audit quality.Â Key words: Integrity, Objectivity, Competence, Confidentiality, Professional Behavior, and Audit Quality